Balancing landscape values and tourism choices : Integrating participatory mapping and the IPBES Values Typology - Solé, Liliana; Hearn, Kyle P.; Witra, Tahjudil; Lechner, Alex M.; Fagerholm, Nora (Springer Nature, 2025)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) Biosphere Reserves aim to balance nature and human coexistence, but increasing tourism challenges landscape management. The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) stresses the importance of understanding stakeholder values for effective management of natural spaces through a typology of intrinsic, instrumental, and relational values. This study applies this IPBES typology to tourism preferences in the Archipelago Sea Biosphere Reserve (ABR) using Public Participation Geographic Information Systems (PPGIS). A 2022 survey gathered data from 690 locals, recreationists, and tourists revealing intrinsic values as the most significant. Locals prioritized intrinsic and relational values, while recreationists and tourists emphasized relational and instrumental values. The study highlights a preference for small-scale tourism that preserves landscapes and heritage, illustrating the complexity of aligning stakeholder values in tourism and conservation. Insights from this research guide policymaking to better accommodate diverse values in protected areas.